Prevalence and Antibiogram Pattern of Some Nosocomial Pathogens Isolated from Hospital Environment in Zaria, Nigeria - Chrinius Hammuel; Edward D. Jatau; Clement M.Z. Whong (Aceh International Journal of Science and Technology)
Many ordinary surfaces and hands of healthcare givers in hospitals are sometimes inadequately decontaminated with routine disinfection techniques. It is necessary to determine the distribution of these pathogens in the hospitals. In this study 160 swab samples were collected from ten different surfaces including nurses’ hand swab, Nurses’ table top, door knob/handle, toilet seat, operation table, sink, stretcher, floor, bedrail, and cupboard. Biochemical tests were used to identify the bacteria. Kirby-Bauer-Clinical and Laboratory Standards Institute (CLSI) modified single disc diffusion technique was used to determine the antibiogram profile of the pathogens at 0.5 scale McFarland’s standard (1.5 × 108 cells/ml). The total percentage prevalence of Staphylococcus aureus was 50.80%, Pseudomonas aeruginosa 28.60% and Escherichia coli 20.60%. Out of 20.60% of E. coli isolates7.7% were found to be E. coli O157:H7. S. aureus isolates were highly resistant to ampcillin and cefoxitin P. aeruginosa and E. coli were resistant to tetracycline. The multiple antibiotic resistance indexes of the pathogens were more than 0.2. Among the isolates, S. aureus showed more multidrug resistance (31.30%) and E. coli had the least multidrug. Frequently touched surfaces within the hospital environment are contaminated by Pseudomonas aeruginosa, Escherichia coli and Staphylococcus aureus. These pathogens can be transfer from surfaces to patients and to surfaces again through healthcare workers. The widespread use of antimicrobials, especially over- or inappropriate use of antibiotics, has contributed to an increased incidence of antimicrobial-resistant organisms.